PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) MELALUI TEKS DRAMA “SULTAN SURIANSYAH” - Noortyani, Rusma; Maghfirah, Alfanida; Maryaeni, Maryaeni; Mu'in, Fatchul (Hiski Malang, 2022)
This study aims to describe the implementation of learning literature to students in class 8C at SMPN 21 Banjarmasin, South Kalimantan, applying the Culturally Responsive Teaching (CRT) approach to the drama text